2016
DOI: 10.1111/resp.12933
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 2 is decreased in peripheral blood pro‐inflammatory CD8+ T and NKT‐like lymphocytes following lung transplant

Abstract: HDAC2 is decreased in CD8+ T and NKT-like pro-inflammatory lymphocytes following lung transplant. Treatment options that increase HDAC2 may improve graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…There was a negative correlation between loss of HDAC2 by CD8 + T cells with FEV 1 and time post‐transplant, findings similar to those in the current study. Previous studies also showed a correlation between loss of GCR and HDAC2, with an increase in the proinflammatory potential of these cells . We now show a loss of HDAC2 by CD8 T, NK T‐like and NK cells in BAL and large and small airways in stable lung transplant patients, suggesting another mechanism of steroid resistance of these cells.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…There was a negative correlation between loss of HDAC2 by CD8 + T cells with FEV 1 and time post‐transplant, findings similar to those in the current study. Previous studies also showed a correlation between loss of GCR and HDAC2, with an increase in the proinflammatory potential of these cells . We now show a loss of HDAC2 by CD8 T, NK T‐like and NK cells in BAL and large and small airways in stable lung transplant patients, suggesting another mechanism of steroid resistance of these cells.…”
Section: Discussionsupporting
confidence: 78%
“…There was a negative correlation between loss of HDAC2 by CD8 + T cells with FEV 1 and time post-transplant, findings similar to those in the current study. Previous studies also showed a correlation between loss of GCR and HDAC2, with an increase in the proinflammatory potential of these cells [10,17]. We Fig.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Measurement of prednisolone levels in these steroid resistance cells would be worthwhile to identify whether intracellular steroid levels are indeed low (and hence due possibly to the increase in Pgp expression). Our recent findings of reduced levels of histone deacetylase 2 in CD8 + T and NK T‐like cells following lung transplant may be a further factor contributing to steroid resistance in these cells, and would be another worthwhile investigation . Nine of the 10 patients with BOS were being treated with a single calcineurin inhibitor, tacrolimus, and it would be worthwhile studying patients being treated with other calcineurin inhibitors such as CsA to determine if Pgp and GCR expression in CD8 + T cells are altered compared with those treated with tacrolimus.…”
Section: Discussionmentioning
confidence: 99%